2014
DOI: 10.3906/zoo-1304-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differentiation among species of the genus Mugil Linnaeus, 1758 (Mugilidae) from Côte d’Ivoire

Abstract: K-shell fluorescence yields ωK were measured for the elements Ti, V, Cr, Fe, Co, Ni, Cu and F and Cl compounds of these elements. Measurements were carried out at 10 keV excitation energy using secondary excitation method. K x-rays emitted by samples were counted by a Si(Li) detector with 160 eV resolution at 5.9 keV. Measurement of K-shell fluorescence yields ωK for these elements are compared with earlier experimental results obtained by other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
2
0
2
Order By: Relevance
“…Thomson, 1997;Camacho-Rodríguez, Lozano-Vilano, 2004), who used non-standardized measurements. Some of the linear measurements of this analysis are consistent with those used in morphological studies for some taxa of the family Mugilidae and have found to be effective for taxonomical discrimination (e.g., Ibáñez-Aguirre, Lleonart, 1996;Cousseau et al, 2005;Ibáñez-Aguirre et al, 2006;González-Castro et al, 2008Konan et al, 2014). These last authors determined for the genus Mugil that the landmarks associated to the head region had a higher discriminative power.…”
Section: Discussionsupporting
confidence: 78%
“…Thomson, 1997;Camacho-Rodríguez, Lozano-Vilano, 2004), who used non-standardized measurements. Some of the linear measurements of this analysis are consistent with those used in morphological studies for some taxa of the family Mugilidae and have found to be effective for taxonomical discrimination (e.g., Ibáñez-Aguirre, Lleonart, 1996;Cousseau et al, 2005;Ibáñez-Aguirre et al, 2006;González-Castro et al, 2008Konan et al, 2014). These last authors determined for the genus Mugil that the landmarks associated to the head region had a higher discriminative power.…”
Section: Discussionsupporting
confidence: 78%
“…A total of 25 traditional morphometric characters were measured in centimeter using a digital caliper to the nearest 0.01 cm (Fig. 2) measurements following some published methods (Ibanez-Aguirre et al, 2006;Katselis et al, 2006;Rezaei et al, 2012;Konan et al, 2014). To minimize human error, all morphological measurements were performed by the same person.…”
Section: Methodsmentioning
confidence: 99%
“…Lokasipengambilan Konan et al, 2014) digunakan untuk identifikasi ikan belanak (Mugillidae) ditampilkan pada Gambar 1. Gambar 1.…”
Section: Materi Dan Metodeunclassified
“…Morfometrik standar (Konan et al, 2014) Ikan diletakkan di atas milimeter blok, yang diberi dasar sterofoam, dengan posisi ikan diatur menghadap ke kiri. Pengukuran panjang standar dilakukan mulai ujung depan moncong sampai pangkal sirip ekor ikan, kemudian diukur jaraknya sesuai dengan pedoman pengukuran morfometrik standar(Gambar 2.)…”
Section: Pengukuran Morfometriunclassified